Reduction of Cystatin B results in increased cathepsin B activity in disomic but not Trisomy 21 human cellular and mouse models - Yixing Wu; Karen Cleverley; Frances K. Wiseman (PLoS ONE, 2025)
Down syndrome, resulting from trisomy of human chromosome 21, is a common form of chromosomal disorder that results in intellectual disability and altered risk of several medical conditions. Individuals with Down syndrome have a greatly increased risk of Alzheimer’s disease (DSAD), due to the presence of the APP gene on chromosome 21 that encodes the amyloid-β precursor protein (APP). APP can be processed to generate amyloid-β, which accumulates in plaques in the brains of people who have Alzheimer’s disease and is the upstream trigger of disease. Cathepsin B has potential roles in both APP processing and amyloid-β degradation and has been suggested to contribute to amyloid-β accumulation. An endogenous inhibitor of Cathepsin B, Cystatin B (CSTB), is encoded on chromosome 21. The abundance of this protein is increased in the brains of individuals with DSAD, which may be associated with a decrease in Cathepsin B activity compared to individuals who have Alzheimer’s disease in the general population. Whether targeting CSTB can modulate Cathepsin B activity in the context of trisomy of chromosome 21 is unclear. Here we test if reducing CSTB can alter Cathepsin B activity in a mouse and a cellular model of trisomy of chromosome 21. We find that reducing CSTB abundance increases Cathepsin B activity in disomic controls but not in the presence of trisomy of chromosome 21. These findings offer new insights into the role of CSTB in regulating Cathepsin B activity.